The effect of dielectric overlay on microstrip antenna embedded in composite laminated substrates. (2nd June 2014) - Yang, S. M.; Hung, C.‐C.
Summary Composite structures with desire mechanical properties can be tailored to embed microstrip antenna for reducing aerodynamic disturbance in aerospace systems. This work aims at developing a spectral domain model to analyze the effect of dielectric overlay on the performance of microstrip antenna embedded in composite laminated substrates. Analysis shows that antenna performance depends not only on the dielectric overlay but also on the laminate layer's electromagnetic property, fiber direction, and stacking sequence. The common belief that the antenna size will be reduced because of the increase of equivalent permittivity by the dielectric overlay is no longer valid in composite laminated substrates. Of the eight substrates studied, overlay can, in general, reduce antenna radiation efficiency; however, it is found to have favorable effect in substrates with some selected electromagnetic properties and stacking sequence. For example, removing the antenna overlay in [45/−45/−45/45/45/−45] substrate can be counterproductive. Copyright © 2014 John Wiley & Sons, Ltd.